On the Dynamics of the Plasma Entry and Guiding in a Straight Magnetized Filter of a Pulsed Vacuum Arc - Giuliani, Leandro Estanislao (2007)
In this paper, a study of the plasma jet generated in a pulsed copper vacuum arc along a straight magnetized filter is presented. The ion saturation current and the plasma potential at different radial and axial positions and magnetic field intensities were measured using electrostatic probes. A theoretical model was developed to understand the dynamics of the plasma entry and guiding in the filter. This model takes into account magnetic field variations and Gaussian ion radial profiles. An analysis of the experimental results with the theoretical model shows that, in our device, as the magnetic field intensity increases along the filter, the plasma motion evolves from a radial compression with a low rotational velocity at the filter entrance to a rotating jet guided along the duct.a pulsed copper vacuum arc along a straight magnetized filter is presented. The ion saturation current and the plasma potential at different radial and axial positions and magnetic field intensities were measured using electrostatic probes. A theoretical model was developed to understand the dynamics of the plasma entry and guiding in the filter. This model takes into account magnetic field variations and Gaussian ion radial profiles. An analysis of the experimental results with the theoretical model shows that, in our device, as the magnetic field intensity increases along the filter, the plasma motion evolves from a radial compression with a low rotational velocity at the filter entrance to a rotating jet guided along the duct.